O Castigo de Latona: as estratégias da Ditadura Militar para os direitos sociais do trabalhador rural: do Estatuto do Trabalhador Rural do governo João Goulart, de 1963, ao Estatuto do Trabalhador Rural de Emílio Médici, de 1973. - Borges, Alexandre Walmott (2019)
The thesis aimed at analysing the modifications made in the agrarian social and production relations with the edition of the Law called ‘Statute of the Rural Workers’, in 1973. The purpose of this research is to investigate and demonstrate in what manner the edition of this Statute represented a legislative strategy of the Brazilian dictatorship to transform social and production relations in the agrarian areas. The hypothesis of the thesis is that this strategic and transformative project of social and production relations from rural areas departed from a legislative production whose apex was the edition of the ‘Statute of the rural Workers’, in 73, creating a new structure of labour relations. The methodology used encompasses the investigation of initial theoretical and conceptual steps as well as the analysis of the lengthy formation of the Brazilian agrarian system and its narrative constructions of the agrarian system´s problems in the decade of 1960´s in order to show the dictatorship´s strategy for the transformations of this agrarian system. At this point, the narrative shows in what way the transformations were the result of a legislative strategy, adjusting social and production relations. The sources used for these steps of the narrative comprise bibliographical references, official statistical material, administrative speeches and sources of statutory law, including, in the latter case, the standards of interpretation provided by the jurists. The expected results were the confirmation of a vertical and hierarchical legislative strategy, causing changes in the agrarian relations. In the end, it is concluded that the Statute adjusted the labour relations to the new legal framework, the Statute of the Rural Worker, in a system paired with the Earth Statute and with the social security law for rural areas, breaking up the traditional resilient forms of existing obligations.